2008
DOI: 10.1186/1476-511x-7-10
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Korean pine nut oil on in vitro CCK release, on appetite sensations and on gut hormones in post-menopausal overweight women

Abstract: Appetite suppressants may be one strategy in the fight against obesity. This study evaluated whether Korean pine nut free fatty acids (FFA) and triglycerides (TG) work as an appetite suppressant. Korean pine nut FFA were evaluated in STC-1 cell culture for their ability to increase cholecystokinin (CCK-8) secretion vs. several other dietary fatty acids from Italian stone pine nut fatty acids, oleic acid, linoleic acid, alpha-linolenic acid, and capric acid used as a control. At 50 μM concentration, Korean pine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 39 publications
4
124
2
Order By: Relevance
“…Secretion of CCK by FA is dependent on FA structure, chain length, degree of unsaturation and whether it is in the free or bound form (Beard Shall et al, 1989, Douglas et al, 1990, Feltrin et al, 2007, Pasman et al, 2008.…”
Section: Cholecystokinin (Cck) Is a Peptide Hormone Reported To Have mentioning
confidence: 99%
“…Secretion of CCK by FA is dependent on FA structure, chain length, degree of unsaturation and whether it is in the free or bound form (Beard Shall et al, 1989, Douglas et al, 1990, Feltrin et al, 2007, Pasman et al, 2008.…”
Section: Cholecystokinin (Cck) Is a Peptide Hormone Reported To Have mentioning
confidence: 99%
“…Previous studies have shown that PinnoThin™ TG is digested to FFA, like similar dietary TG [31]. Furthermore, in the previous PinnoThin™ trial [28], the effects of CCK response took longer to develop for TG (60 minutes) compared to the FFA (30 minutes). Consequently, insufficient time had passed between the intake of the TG capsules and the ad libitum lunch for lipase action to convert sufficient TG to FFA.…”
Section: Effects Of Pinnothin™ Ffa and Tg On Food Intake Feeding Behmentioning
confidence: 99%
“…The effect of pine nut oil on CCK in humans was evaluated in a randomized, double blind, placebo-controlled, cross-over trial [28]. In this study, eighteen overweight, but otherwise healthy, post-menopausal women participated in this study.…”
Section: Effects Of Pinnothin™ Ffa and Tg On Gut Satiety Hormones Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds (50 mg/dose of each FFA) of Pinus koraiensis in human female subjects showed that GLP-1 was higher after 60 minutes of administration [11].…”
Section: Korean Pinementioning
confidence: 99%